2021
DOI: 10.2337/figshare.14691045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipocyte-Specific Deletion of Lamin A/C Largely Models Human Familial Partial Lipodystrophy Type 2

Abstract: Mechanisms by which autosomal recessive mutations in <i>Lmna</i> cause familial partial lipodystrophy type 2 (FPLD2) are poorly understood. To investigate function of lamin A/C in adipose tissues, we created mice with an adipocyte-specific loss of <i>Lmna</i> (<i>Lmna</i><sup>ADKO</sup>). Although <i>Lmna</i><sup>ADKO</sup> mice develop and maintain adipose tissues in early postnatal life, they show a striking and progressive loss of white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a component of the nuclear lamina, lamin A/C is important for maintaining the nuclear envelope functions, and its loss or mutation causes metabolic dysfunction of adipocyte. 15,16 Lelliot et al showed that lamin A/C expression was increased with ex vivo differentiation of human adipocyte cells. 17 Miranda et al reported that lamin A/C mRNA expression was elevated in subcutaneous adipose tissue of obese and type 2 diabetes mellitus patients.…”
Section: Introdutionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a component of the nuclear lamina, lamin A/C is important for maintaining the nuclear envelope functions, and its loss or mutation causes metabolic dysfunction of adipocyte. 15,16 Lelliot et al showed that lamin A/C expression was increased with ex vivo differentiation of human adipocyte cells. 17 Miranda et al reported that lamin A/C mRNA expression was elevated in subcutaneous adipose tissue of obese and type 2 diabetes mellitus patients.…”
Section: Introdutionmentioning
confidence: 99%
“…As a component of the nuclear lamina, lamin A/C is important for maintaining the nuclear envelope functions, and its loss or mutation causes metabolic dysfunction of adipocyte 15,16 . Lelliot et al showed that lamin A/C expression was increased with ex vivo differentiation of human adipocyte cells 17 .…”
Section: Introdutionmentioning
confidence: 99%
“…Other approaches used to explore the relationship between adipocytes and bone have included depletion of these cells using mice expressing diphtheria toxin A (DTA) (9), or DT receptor (DTR) (10) in all adipocytes, or adipocyte-specific deletion of genes related to adipocyte differentiation and lipid formation, such as Pparg (11), Kindlin-2 (12), Cebp and other bZIP family members (13), and Lmna (14). These studies suggest that loss of adipocytes, including BMAds, is associated with significant increases of bone mass; however, interpretation of these data is complicated since white, beige, brown and bone marrow adipocytes are all depleted by Adipoq-or Fapb4-Cre in these animal models.…”
Section: Introductionmentioning
confidence: 99%